La collaboration au cœur du processus de création. Les œuvres réalisées au titre du 1 % artistique dans les lycées de Basse-Normandie (1951-1986) - Sabrina Ducroquet-Blanchet (In Situ)
Since 2012, the ‘Inventaire général du Patrimoine culturel’, a heritage inventory service under the auspices of the Normandy regional council, has been documenting and studying contemporary artworks, created in the framework of the “1 % artistique” programme - a legal obligation in France, founded in 1951, whereby one percent of the budget of public buildings must be devoted to works of art. When architects are appointed for the design of a public building, their mission includes the elaboration of a decorative programme and the choice of the artists to carry it out. This decorative project is presented to a special committee responsible for studying such projects in public buildings, which then approves (or does not approve) the artwork proposed. Ninety-six artworks have been created between 1954 and 1986 for 67 public Lycées (secondary school for 15 to 18 year-olds) in the Calvados, Manche and Orne departments. Some of them are the result of a harmonious collaboration between artists and architects, helped by associations already established, the mutual appreciation of each other’s work, the awareness of the legal obligations of the 1 % programme, the involvement of the stakeholders, or thanks to mutual respect. For other commissions, the dialogue between artists and architects was more complicated. Negative opinions of the committee responsible for the study of the decoration projects in public buildings have sometimes led to a lack of enthusiasm or even a renunciation on the part of the artists and architects. The interventions of the local authorities, interceding on behalf a particular artist or against a particular proposal, have also led to a refusal to carry out the commission or to the permanent abandonment of decorative artworks.